Targeting the pattern‐triggered immunity pathway to enhance resistance to Fusarium graminearum. (6th February 2019) - Sarowar, Sujon; Alam, Syeda T.; Makandar, Ragiba; Lee, Hyeonju; Trick, Harold N.; Dong, Yanhong; Shah, Jyoti
Summary: Fusarium head blight (FHB) is a disease of the floral tissues of wheat and barley for which highly resistant varieties are not available. Thus, there is a need to identify genes/mechanisms that can be targeted for the control of this devastating disease. Fusarium graminearum is the primary causal agent of FHB in North America. In addition, it also causes Fusarium seedling blight. Fusarium graminearum can also cause disease in the model plant Arabidopsis thaliana . The Arabidopsis– F. graminearum pathosystem has facilitated the identification of targets for the control of disease caused by this fungus. Here, we show that resistance against F. graminearum can be enhanced by flg22, a bacterial microbe‐associated molecular pattern (MAMP). flg22‐induced resistance in Arabidopsis requires its cognate pattern recognition receptor (PRR) FLS2, and is accompanied by the up‐regulation of WRKY29 . The expression of WRKY29, which is associated with pattern‐triggered immunity (PTI), is also induced in response to F. graminearum infection. Furthermore, WRKY29 is required for basal resistance as well as flg22‐induced resistance to F. graminearum . Moreover, constitutive expression of WRKY29 in Arabidopsis enhances disease resistance. The PTI pathway is also activated in response to F. graminearum infection of wheat. Furthermore, flg22 application and ectopic expression of WRKY29 enhance FHB resistance in wheat. Thus, we conclude that the PTI pathway provides a target for the control of FHB in wheat. We further show that the ectopic expression of WRKY29 in wheat results in shorter stature and early heading time, traits that are important to wheat breeding.